The Effects of Modest Alcohol Consumption on Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Wongtrakul, Wasit; Niltwat, Sorachat; Charatcharoenwitthaya, Phunchai (Frontiers in Medicine, 2021)
Background and Objective: There is no consensus regarding modest alcohol consumption in patients with non-alcoholic fatty liver disease (NAFLD) due to conflicting results. The aim of this meta-analysis was to examine the effects of modest alcohol consumption on histological severity, histological course, hepatocellular carcinoma, and long-term clinical outcomes in NAFLD patients. Methods: We searched MEDLINE and EMBASE databases from inception to October 2020 for studies evaluating the effects of modest alcohol consumption among patients with NAFLD. A random-effects meta-analysis using pooled odds ratio (OR) and hazard ratio (HR) was calculated with 95% confidence interval (CI). Study quality was assessed with the Newcastle-Ottawa Scale. Results: Fourteen cross-sectional or cohort studies with aggregate data on 14,435 patients were included in the analysis. Modest alcohol consumption resulted in lower risks for steatohepatitis (OR 0.59; 95% CI 0.45-0.78; I2 = 12%) and advanced fibrosis (OR 0.59, 95% CI 0.36-0.95; I2 = 75%). Histological follow-up data showed that modest alcohol use was associated significantly with less steatohepatitis resolution but not with fibrosis progression. The HR for developing hepatocellular carcinoma was 3.77 (95% CI 1.75-8.15; I2 = 0%). NAFLD patients with modest alcohol intake had a lower mortality risk than lifelong abstainers (HR 0.85; 95% CI 0.75-0.95; I2 = 64%). Conclusion: This meta‐analysis suggests that medical advice for modest alcohol drinking should be made cautiously in caring for an individual patient based on the clinical context. Practically, patients with steatohepatitis or advanced fibrosis should avoid alcohol use, whereas patients with low fibrosis risk may be allowed for modest and safe drinking.